ON THE USE OF THE COMMUNICATIVE APPROACH AT SCHOOL LEVEL IN HUALPÉN: A QUALITATIVE STUDY - Muñoz Muñoz, Belén; Chandía Baeza, Mauricio; Véliz Campos, Mauricio (Paideia Revista de Educación, 2020)
The Chilean Ministry of Education frameworks the teaching of English, by and large, in the Communicative Approach (CA). However, the current results show a poor performance between students when using the English language. A communicative curriculum does not assure the use of the language communicatively. This issue has been studied in different countries with similar results. It would be essential to know what it is happening in our national context for future decision-making. This study attempts to determine the degree of congruence between the methodologies used within English classrooms and the tenets proposed by the CA, in three municipal schools in Hualpén. To this end, data was collected from three English language teachers and five students randomly selected from each the three teachers’ classes. A semi-structured interview was used with the former participants and a focus interview with the latter. Also, a content analysis procedure was used to carefully examine the teachers’ lesson plans. The results suggest despite the use of different proposals of the CA, communicative competence is not being enhanced among students who do not have the possibility to use the English language as a communicative tool.